COGNITIVE-BEHAVIORAL THERAPY (CBT) BASED ON STUDENTSâ€™ ACADEMIC PROCRASTINATION BEHAVIOR PROFILE - Farida Coralia; Umar Yusuf; Milda Yanuvianti (Proyeksi: Jurnal Psikologi, 2012)
Academic procrastination is an unnecessary delay behavior conducted in the kinds of academic tasks,such as the final project or thesis. Cognitive Behavioral Therapy (CBT) is a form of psychotherapy aimedat helping individuals cope with the problem through the introduction, identification and modification ofthe contents of individual cognition that does not work (dysfunctional) which may include assumptions,attitudes, and rules are irrational and automatic negative thoughts. The purpose of this study are to getan overview of academic procrastination that occurs at students from faculty of X, in doing their thesis,based on CBT approaches to overcome academic procrastination, especially to overcome the delayscompletion of thesis. This study uses quantitative and qualitative approaches, with purposive samplingtechnique. The study subjects consisted of 32 students from faculty of X whom are working their thesis.Based on Tuckman Procrastination Scale indicated that procrastination experienced by subjects in thecategories of mild, moderate to severe, with most results in the category of being mild and moderate.From the results of in-depth interviews of 14 individuals from 32 subjects, revealed that the wholeÂ subject of procrastination in general display characteristics, namely: delay for a task that should not bedone, and the uncomfortable feeling during the deferment done.